Reflecting Light : What is left on stage. (Gent : KASK School of Arts, 2024)
Csornai, Emese ; Doublier, Henri Emmanuel ; Fedinger, Jan ; Humalisto, Tomi ; Maertens, Jan ; Pocheron, Bruno ; Veldhuis, Ezra ; Coeman, Bram ; Belpaeme, Geert
"The research project Reflecting Light in financed by HOGENT Arts Research Fund and co-financed by BUDA arts centre (Kortrijk), HAUT (Copenhagen) and Mad House (Helsinki)."
Reflecting Light is a fanzine about light and lighting design in the arts.
boek